Sentient Systems and Sensitive Minds: Governing AI in Mental Health - Sangramesh Talukdar; Arkaprava Ghosh (The Bioscan, 2025)
The integration of technology in mental healthcare has evolved significantly, with recent years witnessing the increased adoption of machine-based systems for diagnosis, treatment planning, and patient interaction (Smith & Kumar, 2022). However, this technological shift has outpaced the development of appropriate legal and ethical frameworks, particularly in countries where mental health legislation is still evolving (Patel, 2021). This paper aims to critically examine the legal and ethical dimensions surrounding the use of advanced digital systems in mental health care. It focuses on identifying gaps in existing legal provisions, such as the Mental Healthcare Act, 2017 (Government of India, 2017), and explores the ethical dilemmas posed by automated interventions in therapeutic contexts (Lee & amp; Tan, 2020). The study adopts a qualitative, doctrinal research approach. It involves a detailed review of statutory provisions, judicial interpretations, and scholarly literature related to mental health law and digital health technologies (Jones, 2019). Comparative analysis is also undertaken to explore international best practices and standards (WHO, 2020). The research reveals that current legal frameworks inadequately address issues such as system accountability, liability for harm, and algorithmic transparency (Chakraborty & Mehta, 2021). Ethical challenges include algorithmic bias stemming from non-representative data and the diminishing role of human empathy in care delivery (Nguyen et al., 2023). The lack of comprehensive data protection measures further aggravates concerns over patient privacy and trust (Roy & Singh, 2022). To ensure responsible integration of digital systems in mental health services, a robust regulatory framework is essential. This should include updated legal provisions, ethical oversight, and safeguards for data privacy. Balancing innovation with accountability will be critical in protecting the rights and well-being of individuals seeking mental health care (Desai, 2021).